Prevalence of Risk Factors for Diabetes Mellitus and Hypertension Among Adult in Tabuk- Kingdom of Saudi Arabia (Archives of Clinical and Medical Case Reports, 2018)
Background: The worldwide incidence of diabetes has increased significantly, with the number of people of all ages with diabetes expected to approximately double between 2000 and 2030, and is seen as a major source of disability and health costs. The balance between prevention and intervention, as with other infectious diseases, is the best way to stop the growing burden of cardiovascular disease. Objective: This study evaluates the prevalence of risk factors for diabetes and hypertension in a sample from Tabuk University. Methods: A cross-sectional study was conducted in 2018 with 120 male and female students at Tabuk University (Tabuk, Saudi Arabia) between 20-55 years of age from various departments at Tabuk University. Results: The evaluation was conducted with 120 participants to assess of prevalence for hypertension and diabetes at Tabuk University, where the prevalence rate is already higher than most cities in Saudi Arabia. Ten per cent of participants had high blood sugar and 10 per cent developed problems in this area, with no significant difference between males and females. Conclusion: This study display that cardiovascular risk factors will affect those with major main health disorders in the future. Thus, a national campaign to promote healthy eating, better lifestyles, and physical activity is the priority of health care.